Moving beyond the illusion of participation in the governance of Yangambi Biosphere Reserve (Tshopo Province, Democratic Republic of Congo) - Koy, J.K.; Monga Ngonga, A.M.; Wardell, D.A. (Pensoft Publishers, 2019)
The participation of local communities in the governance of protected areas in the Democratic Republic of Congo is challenged by several external and local factors. This article aims to understand the representation of local communities and factors that influence their participation in the governance of the Yangambi Biosphere Reserve. Three principal sources of information (archival records, focus group and semi-structured interviews) were used to collect data. The results indicate a top-down participatory approach. The cumulative failure of several projects in the context of local development has led to different perceptions by local communities of their role in the participative governance of Yangambi Biosphere Reserve. Initiatives in participatory management and local development only function during the lifetime of externally-funded projects when initiators are present in the intervention area. The results call into question formal claims made by both conservation projects and the Congolese government regarding the actual participation of local communities in the governance of Biosphere Reserves. Furthermore, although Biosphere Reserves in DRC are recognized as part of the national network of protected areas since 2002, their management is still not aligned to either the Seville Strategy or the statutory framework of the world network of Biosphere Reserves. To achieve this, local development initiatives need to focus on poverty alleviation (through the diversification of income sources, entrepreneurship, farmer training and the creation of employment opportunities) and a better understanding of local practices and cultures in the design of such projects.